Peningkatan Keterampilan Konseling melalui Pelatihan Online Strategi Motivational Interviewing (MI) bagi Konselor Sekolah di Kota Semarang - Mulawarman,; Luthfi Fathan Dahriyanto,; Eni Rindi Antika,; Edwindha Prafitra Nugraheni,; Vira Mulyawati,; Vrimadieska Ayuanissa Waluyan, (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
The aim of this community service is to train counselors or counseling teachers to improve counseling skills in schools by using a motivational interviewing (MI) strategy to students. MI Strategies were trained to 31 high school counselors in Semarang City. This training was held for three days with an online process using the Zoom Cloud Meetings application and Google Classroom. To measure the understanding and technical abilities of school counselors in applying the motivational interviewing strategy, researchers used the motivational interviewing instrument. Based on the training results, it shows that there is a significant difference in the ability of the counselor before and after being given the motivational interviewing training.